Biblical evidence from Obadiah and Psalm 137 for an Edomite treaty betrayal of Judah in the sixth century B.C.E. - Dykehouse, Jason (2013)
Fil: Dykehouse, Jason. South Texas School of Christian Studies; Estados Unidos